2015
DOI: 10.4103/2231-0762.164788
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS awareness among Iraqi medical and dental students

Abstract: Objectives:The present study investigated the awareness of HIV/AIDS among medical and dental students in four provinces of Iraq, a country with low HIV/AIDS frequency.Materials and Methods:In the present study, the target population was all Iraqi medical and dental students who were in 3rd and 4th year of their education. Out of 15 medicine and 10 dentistry faculties in Iraq, 4 medical and dental faculties were randomly selected. All the students under them were invited to participate in the study (600 student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 19 publications
6
23
0
2
Order By: Relevance
“…14 As to dentists may be more prone to be exposed to cross-infection, the reported percentages (89% of pre-clinical and 93.3% of clinical students) are aligned with those reported in the literature. 13,15 The positive response (20% and 16.8%, respectively to the student' group) on saliva as being a possible mean to transmit HIV reported in the present study is in agreement with that observed by Ellepola et al (6% and 24%). 16 23 However, other studies have shown that most of the assessed dental students believed that handpiece aerosols can transmit HIV.…”
Section: Onsupporting
confidence: 93%
See 3 more Smart Citations
“…14 As to dentists may be more prone to be exposed to cross-infection, the reported percentages (89% of pre-clinical and 93.3% of clinical students) are aligned with those reported in the literature. 13,15 The positive response (20% and 16.8%, respectively to the student' group) on saliva as being a possible mean to transmit HIV reported in the present study is in agreement with that observed by Ellepola et al (6% and 24%). 16 23 However, other studies have shown that most of the assessed dental students believed that handpiece aerosols can transmit HIV.…”
Section: Onsupporting
confidence: 93%
“…16 23 However, other studies have shown that most of the assessed dental students believed that handpiece aerosols can transmit HIV. 5,13,15 Regarding the heterogeneity in the answers obtained on The present study had a non-response rate of 59.4%. This nonresponse rate was higher than the one expected in electronic surveys.…”
Section: Onmentioning
confidence: 50%
See 2 more Smart Citations
“…Hamid Albujeer et al [7] in their study among Iraqi medical and dental students' knowledge about HIV/AIDS awareness, said that Knowledge of about half of the medical students (54%) was at an intermediate level and of 27.1% students was at a good level; more than half of the dental students (68.2%) had an intermediate level, and 10.5% had a good level of knowledge. …”
Section: Need For the Studymentioning
confidence: 99%